Deficient CD4+CD25+ T regulatory cell function in patients with abdominal aortic aneurysms - Yin, Mingdi; Zhang, Jian; Wang, Yong; Wang, Shaoye; Böckler, Dittmar; Duan, Zhiquan; Xin, Shijie (Arteriosclerosis, thrombosis, and vascular biology, 2010)
Objective— Increasing evidence shows that autoimmune response contributes importantly to pathogenesis of abdominal aortic aneurysm (AAA). This work was aimed to assess the possibly altered function of peripheral CD4+CD25+ T regulatory cells (Tregs) that might breakdown immunologic self-tolerance in AAA patients. - Methods and Results— Peripheral blood from 22 AAA patients, 11 patients with abdominal aortic atherosclerotic occlusive disease (AOD), and 32 healthy controls (HCs) was analyzed to determine the percentage of CD4+CD25+ Tregs in the total CD4+ T-cell population and FOXP3 expression by means of flow cytometry. The frequencies of the CD4+CD25+ Treg population were not significantly different between groups (AAA, 5.69±0.99%; AOD, 5.52±1.13%; HC, 5.88±1.55%; P>0.05). However, the frequency of CD4+CD25+FOXP3+ T cells in AAA patients (2.45±0.57%) was significantly lower than that in AOD group (3.41±0.72%; P<0.01) or in HCs (3.69±0.82%; P<0.01). A comparison of FOXP3 mRNA and protein expression revealed significantly lower levels in CD4+CD25+ Tregs from AAA group than either of other 2 groups (P<0.01). Suppressive function assay showed that freshly isolated CD4+CD25+ Tregs from patients with AAA exhibited significantly less suppressive activity than those from AOD patients or HCs (P<0.01). Mixing cultures with CD4+CD25+ T cells and CD4+CD25− T cells from AAA patients and HCs demonstrated that the primary regulatory defect is due to a dysfunction of CD4+CD25+ Tregs, and not a resistance of CD4+CD25− responder T cells to suppression in AAA patients. - Conclusion— Our data demonstrate a reduced level of FOXP3 expression in peripheral CD4+CD25+ Tregs and decreased frequency of CD4+CD25+FOXP3+ T cells in a cohort of AAA patients enrolled in the study, which leads to a functional deficiency of CD4+CD25+ Tregs as a whole. This indicates an impaired immunoregulation by Tregs that may contribute to AAA pathogenesis.
Published online May 6, 2010
Gesehen am 03.07.2024
Die Pluszeichen im Titel sind hochgestellt